Influence of parent graphite particle size on the electrochemistry of thermally reduced graphene oxide - Chee, Yin Sze (2013)
Electrochemical applications of graphene are of very high importance. For electrochemistry, bulk quantities of materials are needed. The most common preparation of bulk quantities of graphene materials is based on oxidation of graphite to graphite oxide and subsequent thermal exfoliation of graphite oxide to thermally reduced graphene oxide (TR-GO). It is important to investigate to which extent a reaction condition, that is, composition of the oxidation mixture and size of graphite materials, influences the properties of the resulting materials. We characterised six graphite materials with a range of particle sizes (0.05, 11, 20, 32, 35 and 41 μm) and the TR-GO products prepared from them by use of scanning electron microscopy, Raman spectroscopy and X-ray photoelectron spectroscopy. Cyclic voltammetric performance of the TR-GO samples was compared using ferro/ferricyanide and ascorbic acid. We observed no correlation between size of initial graphite and properties of the resultant TR-GO such as density of surface defects, amount of oxygen-containing groups, or rate of heterogeneous electron transfer (HET). A positive correspondence between HET rate and high defect density as well as low amounts of oxygen functionalities was noted. Our findings will have profound influence upon practical fabrication of graphene for applications in sensing and energy storage devices.